2021
DOI: 10.3389/fonc.2021.775363
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Pathogenetic Concepts in T-Cell Prolymphocytic Leukemia and Their Translational Impact

Abstract: T-cell prolymphocytic leukemia (T-PLL) is the most common mature T-cell leukemia. It is a typically aggressively growing and chemotherapy-resistant malignancy with a poor prognosis. T-PLL cells resemble activated, post-thymic T-lymphocytes with memory-type effector functions. Constitutive transcriptional activation of genes of the T-cell leukemia 1 (TCL1) family based on genomic inversions/translocations is recognized as a key event in T-PLL’s pathogenesis. TCL1’s multiple effector pathways include the enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Additional studies are required to predict such genes. A promising strategy would be the analysis of genome-wide T-PLL-specific gene regulatory networks with the help of network flow algorithms to identify subgroup-specific driver candidates [5]. The value of such approaches has already been demonstrated for other types of cancer [67][68][69].…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations
“…Additional studies are required to predict such genes. A promising strategy would be the analysis of genome-wide T-PLL-specific gene regulatory networks with the help of network flow algorithms to identify subgroup-specific driver candidates [5]. The value of such approaches has already been demonstrated for other types of cancer [67][68][69].…”
Section: Plos Onementioning
confidence: 99%
“…T-cell prolymphocytic leukemia (T-PLL) is a rare but highly malignant mature T-cell leukemia with aggressive clinical course and high mortality rates [1][2][3][4][5]. T-PLL was first described by [6] almost 50 years ago.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Improved understanding of T-PLL pathogenesis has exposed novel vulnerabilities that are currently being explored pre-clinically and in early-phase clinical trials (Table 5), some of which have been recently reviewed [72,73], and have been identified in an unbiased ex vivo drug screen [47]. These novel therapeutic strategies (represented in Figure 4), informed by an improved understanding of T-PLL pathogenesis, suggest that we may be on the dawn of a new era in T-PLL management.…”
Section: Novel Therapies and Future Therapeutic Strategiesmentioning
confidence: 99%